Screening of esophageal varices in children using esophageal capsule endoscopy: a multicenter prospective study - Cardey, Jacques; Le Gall, Catherine; Michaud, Laurent; Dabadie, Alain; Talbotec, Cécile; Bellaiche, Marc; Lamireau, Thierry; Mas, Emmanuel; Bridoux-Henno, Laure; Viala, Jerome; Restier-Miron, Lioara; Lachaux, Alain (Endoscopy, 2019)
Background Esophagogastroduodenoscopy (EGD) is the standard method for diagnosis of esophageal and gastric varices in children. In this prospective study we evaluated the use of PillCam esophageal capsule endoscopy (ECE) in pediatric patients. Methods Patients aged 7 to 18 years presenting with portal hypertension and/or cirrhosis underwent ECE (PillCam ESO 2, Given Imaging Ltd.) followed by EGD. Results 102 patients were screened, 81 (52 boys; mean age 13.96 ± 0.25 years) were included and 21 were excluded (16 for “candy test” failure). Esophageal varices were identified by EGD in 62 patients (77 %) and by ECE in 57 patients (70 %) using the de Franchis classification (DFC). The sensitivity of ECE for esophageal varices was 92 % and the specificity was 100 % using DFC. Based upon 57/81 patients with small, medium, and large varices on both ECE and EGD, using DFC, the sensitivity, specificity, positive (PPV) and negative predictive value (NPV) were 55 %, 92 %, 89 %, and 63 %, respectively, giving a total overall accuracy of 72 %. To improve sensitivity and specificity in classification of esophageal varices, we propose using a modified score. This score detected esophageal varices with 100 % sensitivity, 93 % specificity, 94 % PPV, and 100 % NPV, giving a total overall accuracy of 97 %. All patients preferred ECE over EGD. No capsule retention was recorded.Conclusions ECE is a well-tolerated and safe procedure in children. Using the modified score, the sensitivity of ECE is currently sufficient to detect esophageal varices and replace EGD in infants with suspicion of esophageal varices or when EGD is refused.